2018
DOI: 10.1002/jsde.12019
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nano‐Polymer Emulsion for Inhibiting Shale Self‐Imbibition in Water‐Based Drilling Fluids

Abstract: In order to effectively solve shale instability problems in the drilling process, the remarkable capillary effect of shale formations cannot be ignored. In this paper, we report the development and characterization of a nanopolymer emulsion (SDPE) as a shale self-imbibition control agent in water-based drilling fluids. Spontaneous imbibition experiments, surface tension measurements, contact angle measurements, particle size distribution analysis, linear swelling tests, and hot-rolling cuttings dispersion test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It is observed that 0.7 g of T80ZnO optimized the PV, YP, GS, filtrate loss volume, and lubricious properties in drilling fluid; therefore, it can provide multiple benefits such as adequate drilling speed, improved cutting lifting efficiency, sustained adequate hydrostatic pressure, reduced loss of drilling fluid, minimized wellbore instability, and improved clay swelling inhibition. To enhance the aforementioned properties, several members of the carbon nanomaterials family, , inorganic metal oxides nanomaterial, , organic nanomaterial, and nanostarch , have been widely used in water-based drilling …”
Section: Results and Discussionmentioning
confidence: 99%
“…It is observed that 0.7 g of T80ZnO optimized the PV, YP, GS, filtrate loss volume, and lubricious properties in drilling fluid; therefore, it can provide multiple benefits such as adequate drilling speed, improved cutting lifting efficiency, sustained adequate hydrostatic pressure, reduced loss of drilling fluid, minimized wellbore instability, and improved clay swelling inhibition. To enhance the aforementioned properties, several members of the carbon nanomaterials family, , inorganic metal oxides nanomaterial, , organic nanomaterial, and nanostarch , have been widely used in water-based drilling …”
Section: Results and Discussionmentioning
confidence: 99%
“…The shale surface is usually hydrophilic, and capillary force is one of the driving forces for water to invade the shale formation. As shown in formula , the capillary force is proportional to the surface tension, so reducing the surface tension will help reduce the water intake of shale, thereby weakening the hydration of shale. , where p c is the capillary force (Pa), σ is the surface tension of the testing fluid (mN m –1 ), θ is the contact angle (deg), and r is the pore-throat radius of shale sample (mm).…”
Section: Resultsmentioning
confidence: 99%
“…A contact angle greater than 90° indicated that the shale surface changed from hydrophilic to hydrophobic. Therefore, the adsorption of CA on the surface of the shale greatly changed its wettability, which can effectively reduce the capillary effect of shale . At the same time, the hydrophobic shale surface can significantly reduce water adsorption and prevent shale hydration swelling and dispersion and is conducive to the stability of shale.…”
Section: Resultsmentioning
confidence: 99%